Diagnosis & Tatalaksana Nekrosis Avaskular Caput Femur - Purwanto, Tito; Utami, Winda Trijayanthi (Medula, 2026)
Avascular necrosis (AVN) of the femoral head is a condition resulting from compromised blood supply, leading to bone tissue death and progressive joint damage. Early diagnosis is challenging because initial radiographic findings are often normal, and most patients present at advanced stages. This narrative review discusses the etiology, diagnosis, classification, and treatment options for AVN based on disease stages, highlighting conservative approaches, biological interventions, and surgical procedures. Causes of AVN include alcohol consumption, corticosteroid use, trauma, anatomical abnormalities, and certain hematologic conditions. MRI is the most sensitive diagnostic modality in early phases, while the Ficat & Arlet classification is used for staging. In the pre-collapse phase, conservative management such as protected weight-bearing, bisphosphonates, anticoagulants, prostaglandin analogs, and hyperbaric oxygen therapy may help preserve the joint. Surgical interventions such as core decompression with or without bone grafting and the addition of biological agents aim to enhance angiogenesis and osteogenesis. In the post-collapse phase, joint preservation is not recommended, and total hip arthroplasty is the preferred treatment, although failure rates are higher than in non-AVN osteoarthritis cases. The prognosis of AVN depends on early detection and stage-appropriate intervention. A multimodal approach in the early phase may maintain joint integrity, while in advanced disease, joint reconstruction through arthroplasty provides the most effective outcome. Further evaluation of biological therapies and optimization of rehabilitation strategies are needed to improve clinical results.